Art, Nature, and Culinary as Leverage of Village Branding at the Foot of the Mountain - Soerjo Wido Minarto; Rully Aprilia Zandra; Adzrool Idzwan Ismail (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2021)
Beach tourism and seaside settlements are perennially popular. Nature's potential as well as the coast's characteristic hybrid art may always entice visitors. The settlements at the foot of the mountain, on the other hand, have their own unique environmental, gastronomic, and cultural identities. Bedugul village (Indonesia), Albarracin village (Spain), Reine village (Norway), Wengen village (Switzerland), Panglipuran village (Indonesia), Hallstatt village (Austria), Patiangan village (Indonesia), and Ora village (Indonesia) are some of the names given to the villages in Indonesia (Greece). They're all mountain communities that have successfully marketed themselves as tourist destinations at the foot of the mountain. The goal of this research is to come up with a viable approach for village branding at the foot of the mountain. This study is a hybrid of action research and development research, with a focus on tourism village acceleration. The Benjor village residents, Benjor village administrators, and a sample of potential visitors were polled for information. The community around Benjor village, the Malang Regency community, and persons outside the Malang Regency were all surveyed for potential visitors. Individual interviews or focus groups, environmental observations, and archives of village office records and Malang Regency government documents were used to gather data. The purpose of this study is to understand the tourism village process before and after therapy. Mining potential excavation yields eleven environmental assets in the form of waterfalls, five culinary assets in the form of chilli sauce, grilled rice, and other similar dishes, and three cultural assets in the form of hadrah, jaranan, and dancing. The development research yielded seven goods that Benjor villagers found to be the most effective in terms of branding. For mountain slope communities, the greatest method is to combine branded items that showcase their artistic, natural, and gastronomic potential.